INVESTIGATION OF INFLUENCE OF THE SEA CUCUMBER DISINTEGRATION IN THE PROCESS OF CRYOPROCESSING ON NUTRITIONAL VALUE OF ITS DRY CONCENTRATE - V. D. Bogdanov; A. A. Simdiankin; A. V. Nazarenko (Известия ТИНРО)
Influence of shredding on molecular weight and biological value of dry concentrate is investigated for the sea cucumber Stichopus japonicus from the Severnaya Bay (Peter the Great Bay, Japan Sea). Size of particles of the shredded tissue depends on temperature of freezing: the lower the temperature, the smaller the particles. This dependence affects on intensity of the freeze-drying: decreasing of the raw material temperature from minus 5 to minus 30 оC causes the water content lowering in 1.7 times. The freezing and subsequent shredding have destructuring effect on the protein macromolecules, primarily collagens of the muscles, that contributes to their better absorption by human organism. In the crushed sample, the high-molecular proteins have lower molecular weights, the medium-molecular proteins are almost absent, and the low-molecular proteins are presented by fractions with molecular weight 15 and 50 kDa. The freeze-drying itself contribution to lowering of the proteins molecular weight is evaluated as insignificant. The optimal size of the particles after disintegration is 4–50 μm — this size provides the highest biological value of the dry sea cucumber concentrate.